2023
DOI: 10.3390/ma16186213
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of pH Value and Release of Calcium Ions in Calcium Silicate Cements: An In Vitro Comparative Study

Rubén Herrera-Trinidad,
Pedro Molinero-Mourelle,
Manrique Fonseca
et al.

Abstract: The goal of this study was to evaluate the pH and the release of calcium from four calcium-silicate-based cements. Methods: Four materials were tested (ProClinic MTA; Angelus MTA; ProRoot MTA; Biodentine). The palatal canal root of acrylic upper molars was filled with each cement. Afterwards, they were set in phosphate-buffered saline. Measurements were taken by atomic adsorption spectroscopy (AAS) at 3, 24, 72, 168, 336, 672, and 1008 h. The pH was measured at the same timepoints. Kruskal–Wallis tests were ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…However others found no statistically significant difference in antifungal efficacy for C. albicans between ProRoot MTA, and Biodentine [53] . In contrast, other authors found no difference in antibacterial activity against E. faecalis between them [52,54,55] .…”
Section: Methodsmentioning
confidence: 76%
See 1 more Smart Citation
“…However others found no statistically significant difference in antifungal efficacy for C. albicans between ProRoot MTA, and Biodentine [53] . In contrast, other authors found no difference in antibacterial activity against E. faecalis between them [52,54,55] .…”
Section: Methodsmentioning
confidence: 76%
“…It was found that Biodentine showed significantly higher pH and calcium ion release compared to ProRoot [50,51] . But Rubén Herrera-Trinidad et al reported that the pH values and Ca release increased in the Biodentine group at 168 h [52] .…”
Section: Methodsmentioning
confidence: 90%